Propriedades magnéticas quase-estáticas de filmes ferromagnéticos amorfos de FeCuNbSiB - Alves, Tibério Magno de Lima (2012)
Today, one of the topics that attracts interest of the scientific community is the understanding of magnetic properties of magnetic systems with reduced dimensions, in particular, ferromagnetic thin films. In this case, the comprehension and control of these properties, as well as the development of routes to obtain them, are crucial issues in many aspects of current and future technologies for storage and transmission of information in the electro-electronic industry. There are several materials that exhibit soft magnetic properties, and we highlight the amorphous alloys and that ones obtained by partial crystallization, so-called nanocrystalline materials. The production of these alloys as magnetic ribbons is very common in scientific and technological area, but there are just a few works related to the production of these alloys as thin films. In this work, we studied the quasi-static magnetic properties of ferromagnetic thin films based on FeCuNbSiB in a wide range of thicknesses, from 20 to 500 nm, produced by sputtering. In particular, after the structural characterization performed via X-ray diffraction, the magnetic properties of the sets of samples were investigated using experimental magnetization curve, obtained using a vibrating sample magnetometer, as well as through theoretical curves obtained by theoretical modeling and numerical computation. The modeling process is based on the Stoner Wohlfarth model applied to three dimensions, and adds some energy terms, using as reference experimental results of magnetization. In this case, from the comparison between theoretical and experimental results and the analysis of the constant anisotropy behavior as a function of film thickness, we aim to obtain further information on the magnetization process of the samples, to identify routes for the production of thin films and develop a theoretical to films to use it, in the future, in the obtainment of the theoretical curves of some magnetic measurements, such as magnetoimpedance and magnetoresistance